Genome-Wide Analysis Identifies Rag1 and Rag2 as Novel Notch1 Transcriptional Targets in Thymocytes - Dong, Yang; Guo, Hao; Wang, Donghai; Tu, Rongfu; Qing, Guoliang; Liu, Hudan (Frontiers in Cell and Developmental Biology, 2021)
Recombination activating genes 1 (Rag1) and Rag2 are expressed in immature lymphocytes and essential for generating the vast repertoire of antigen receptors. Yet the mechanisms governing the transcription of Rag1 and Rag2 remain to be fully determined, particularly in thymocytes. Combining cDNA microarray and ChIP-seq analysis, we identify Rag1 and Rag2 as novel Notch1 transcriptional targets in acute T-cell lymphoblastic leukemia (T-ALL) cells. We further demonstrate that Notch1 transcriptional complexes directly bind the Rag1 and Rag2 locus in not only T-ALL but also primary double negative (DN) T cell progenitors. Specifically, dimeric Notch1 transcriptional complexes activate Rag1 and Rag2 through a novel cis-element bearing a sequence-paired site (SPS). In T-ALL and DN cells, dimerization-defective Notch1 causes compromised Rag1 and Rag2 expression; conversely, dimerization-competent Notch1 achieves optimal upregulation of both. Collectively, these results reveal Notch1 dimerization-mediated transcription as one of the mechanisms for activating Rag1 and Rag2 expression in both primary and transformed thymocytes. Our data suggests a new role of Notch1 dimerization in compelling efficient TCR rearrangements in DN progenitors during T cell development.